Early catheter removal following laparoscopic radical hysterectomy for cervical cancer: assessment of a new bladder care protocol. (3rd October 2017) - Campbell, Patrick; Casement, Maire; Addley, Susan; Dobbs, Stephen; Harley, Ian; Nagar, Hans
Abstract: Evidence to support prolonged catheterisation after radical hysterectomy is lacking. We sought to assess feasibility of a new protocol of early post-operative catheter removal following laparoscopic radical hysterectomy for cervical cancer. A retrospective review of post-operative bladder care in patients who underwent laparoscopic radical hysterectomy for cervical cancer was carried out. The post-operative bladder care protocol recommended catheter removal after 24–72 hours. Three consecutive post-void residual scans of less than 150 millilitres (ml) were considered evidence of normal voiding function. First line management of voiding dysfunction was clean intermittent self-catheterisation (CISC). Ninety-eight patients underwent laparoscopic radical hysterectomy for cervical cancer of whom 78 patients had catheter removal 24–72 hours post-operatively. The incidence of post-operative voiding dysfunction in this group was 44%, of whom 88% were managed with CISC and 82% regained normal voiding function. Average hospital stay was 4.2 days. The overall rate of long-term voiding dysfunction was 6%. Early catheter removal after laparoscopic radical hysterectomy appears to be both feasible and effective and compliments the ethos of enhanced patient recovery.